2022
DOI: 10.1186/s12887-022-03120-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in the medical and surgical treatment of necrotizing enterocolitis. A systematic review

Abstract: Background The aim of this review was to identify relevant randomized controlled trials (RCTs) and non-RCTs to evaluate the existing knowledge on the effect of antibiotic treatment for infants with necrotizing enterocolitis (NEC). Objective Identifying 1) the best antibiotic regimen to avoid disease progression as assessed by surgery or death, 2) the best antibiotic regimen for infants operated for NEC as assessed by re-operation or death. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…NEC treatment includes the use of broad-spectrum antibiotics, among which are clindamycin or metronidazole that target anaerobic bacteria [48]. Although one study has reported a significant association between C. butyricum-linked NEC and antibiotic administration [48], there are no data regarding the antimicrobial susceptibility of C. neonatale clinical isolates. Our data support the need, in future studies, to evaluate C. neonatale susceptibility to antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NEC treatment includes the use of broad-spectrum antibiotics, among which are clindamycin or metronidazole that target anaerobic bacteria [48]. Although one study has reported a significant association between C. butyricum-linked NEC and antibiotic administration [48], there are no data regarding the antimicrobial susceptibility of C. neonatale clinical isolates. Our data support the need, in future studies, to evaluate C. neonatale susceptibility to antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in strain NEC86, we identified in silico a gene encoding a 23S rRNA methyltransferase ermQ gene described to provide resistance to macrolides. NEC treatment includes the use of broad-spectrum antibiotics, among which are clindamycin or metronidazole that target anaerobic bacteria [48]. Although one study has reported a significant association between C. butyricum-linked NEC and antibiotic administration [48], there are no data regarding the antimicrobial susceptibility of C. neonatale clinical isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre‐term and low birth weight infants are frequently given antibiotics, but these treatment practices and types of antibiotics administered are dependent on the severity of their clinical symptoms and are highly variable (Gill et al., 2022 ; Sadeghirad et al., 2018 ). Our experimental model tests vancomycin, which is one of the antibiotics given to infants to prevent and treat diseases such as necrotising enterocolitis.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference between the three regimens [28]. Other meta-analyses have confirmed that there is not enough evidence on the type of antibiotics, route of administration or duration of treatment [29 ▪▪ ,30]. The NICU Antibiotics and Outcomes (NANO) trial is an ongoing trial looking at empiric antibiotics (ampicillin and gentamicin) to determine if the rate of NEC is changed when compared with placebo treatment in ELBW infants [31].…”
Section: Antibiotic Treatment Of Complicated Intra-abdominal Infectionsmentioning
confidence: 99%